STREAMFLOW AND SUSPENDED SEDIMENT LOAD TRENDS IN TROTUȘ DRAINAGE BASIN: GEOMORPHIC IMPLICATIONS - DUMITRIU Dan (Present Environment and Sustainable Development, 2020)
The research focusing on the trends of the streamflow and suspended sediment, as well as on the controls involved in these changes, are currently topics of significant interest in fluvial geomorphology. In this context, the aim of this study is to analyze the trends of the streamflow discharge and the sediment load based on a geomorphological approach of the relations between the two variables. These trends were assessed based on three testing methods frequently employed in hydro-geomorphological studies (Mann–Kendall trend test, Șen's slope estimator and the innovative trend method) applied on data from 10 gauging stations located on major tributaries of Trotuș River. Results reveal an overall downward trend of the mean annual streamflow and an increasing trend of the mean annual suspended sediment load. Whereas the decreasing streamflow trend was linked to the diminishing precipitation amounts, the upward trend of suspended sediment load was related to the changes occurring within river channels as a result of flood events.